From the Ground Up: Critical Reflections About Co-Constructing A New Non-Profit Sector Undergraduate Certificate - DeSantis, Gloria C.; Tremka, Angela N. (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2022)
Community-university engagement is a growing field and takes many different forms. We explain and reflect critically on a community-university developmental process that we created to design a new non-profit studies undergraduate certificate. A steering group comprising students, non-profit organizations (NPOs), and faculty guided our process. We adopted a community-based, emergent, multi-tactic process that went from testing an idea, to collectively designing and co-constructing the certificate to building momentum to operationalize it, over an 18-month period. Our strategy was based on the convergence of three main bodies of literature—community-engaged scholarship, citizen participation, and naturalistic inquiry—and included seven tactics: community-university dialogues, e-communication, interactive booths in public places, presentations and learning circles, student research projects, student and NPO surveys, and pilot-testing undergraduate courses. The outcomes of our process revealed strong community support for a new certificate, which was then co-constructed and later approved by the University Senate. Today, five years later, we reflect on the ebb and flow of our process, in particular: emergent design challenges, the space-in-between, community/university black boxes, ownership, and facilitation work. This exploration contributes to the knowledge base on co-construction processes.